Albumin-based Nanoparticles as Promising Drug Delivery Systems for Cancer Treatment - Esim, Ozge; Hascicek, Canan (Current Pharmaceutical Analysis, 2021)
Albumin is an ideal material for the production of drug carrier nanoparticular systems since it is a versatile and functional protein that has been proven to be biodegradable and biocompatible, non-toxic, and immunogenic. Albumin nanoparticles are of great interest as they have the high binding capacity to many drugs with different physicochemical and structural properties and are well tolerated without any side effects. In this review, different types of albumin, special nanotechnological techniques for the production of albumin nanoparticles, such as desolvation, emulsification, thermal gelation, nano-spray drying, and self-assembly, as well as the characterization of albumin nanoparticles, such as particle size, surface charge, morphological properties, drug content, and release profile have been discussed. In addition, the in vitro and in vivo studies of albumin nanoparticles intended both diagnostic and therapeutic usage have been investigated.
Keywords: characterization of nanoparticles